2019
DOI: 10.2185/jrm.3017
|View full text |Cite
|
Sign up to set email alerts
|

A novel unidirectional porous β-tricalcium phosphate grafting for vertebral fracture in the elderly: preliminary case series

Abstract: Objective: To treat vertebral fractures with posterior wall injury in the elderly, vertebral bone grafting is generally performed through a posterior transpedicular approach, combined with pedicle screw fixation. An autologous bone is ideal to treat this disorder. However, harvesting autologous bones from the elderly with osteoporosis is limited by the amount and quality of available autologous bone. Thus, we developed a bone-grafting substitute. The newly developed unidirectional porous β-tricalcium phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Despite its β-TCP composition, the porosity and structure of UDPTCP ensure balanced bone formation and resorption, promoting early remodeling for sustained bone stability and functional recovery [7]. Moreover, the application of UDPTCP extends beyond the tibia, with successful outcomes in spinal surgeries and filling bone defects post-tumor excision reported previously [9][10][11][12]. These cases highlight the bone resorption capacity of UDPTCP starting within three months, with almost complete remodeling in six months to one year.…”
Section: Discussionmentioning
confidence: 82%
“…Despite its β-TCP composition, the porosity and structure of UDPTCP ensure balanced bone formation and resorption, promoting early remodeling for sustained bone stability and functional recovery [7]. Moreover, the application of UDPTCP extends beyond the tibia, with successful outcomes in spinal surgeries and filling bone defects post-tumor excision reported previously [9][10][11][12]. These cases highlight the bone resorption capacity of UDPTCP starting within three months, with almost complete remodeling in six months to one year.…”
Section: Discussionmentioning
confidence: 82%
“…Izawa et al [6] used Affinos ® in 4 cases of calcaneal fractures and reported that its resorption started at 3 months after surgery and replaced to host bone at 6 months in the earliest case. Funayama et al [7] used Afinos ® in 5 cases of burst vertebral fractures, showing that it was replaced to host bone at 3 months postoperatively in one case, and in other 4 cases, the resorption started at 3 months postoperatively and completed at 12 months. It suggested that Affinos has good properties of material resorption and replacement to host bone.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported favorable outcomes with the use of β-TCP for bone defects. Despite only a small number of case reports being available, Affinos has been reported to be used successfully in clinical cases 11 13 . The present study also showed that Affinos maintains a balance between material resorption and trabeculation through the defect, resulting in stable clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%